Law and economic development: current issues - Batievskaia V. B., Kelekhsaeva M. V., Sitokhova T. E., Minakov A. V., Kruglov V. N., Kiselev A. A., Borovkova V. A., Borovkova V. A., Zolotareva I. V., Airikh G. E., Kurov A. E., Lykova O. A., Siziakina M. S., Soldatova L. I., Shmidt I. I., Shaibakova L. F., Chechulina O. A., Belostotskaia A. A., Shchankina L. N., Garnaia ivanova I. A., Serebrennikova A. V., Burtseva E. V., Medvedeva S. V. (Law and economic development: current issues, 2023)
information security is an important part of the country's economic security. At present, the economies of many countries are experiencing an increase in the influence of cybercrime on them, since there are various crimes related to data theft, fraud, account hacking, cyber-attacks by criminals operating in the information field both for financial gain and for terrorist purposes, negatively affecting the security of the financial system and the stability of the economies of countries, including Russia. Therefore, the government, business and the whole society must take various steps to combat threats in the field of information technology.
Keywords: экономическая безопасность; информационная безопасность; защита информации; information security; economic security; information protection; киберугрозы; конфиденциальность данных; защита данных; cyber threats; data privacy; data protection